Contrastive modelling of the intonation of recapitulatory echo interrogative sentences in modern American English and Cuban Spanish - Garcia Romero, Gilberto (2013)
Human speech communication is rich in expressive stylistic, syntactic, lexical and discourse devices which are commonly used to express feelings, attitudes and volitions. Supported by the important contributions of CDA, discourse intonation, discourse semantics and pragmatics this dissertation presents a broad contrastive analysis of the intonation patterns of recapitulatory echo interrogatives in Cuban Spanish and American English. A corpus-driven methodology stresses the importance of prosodic features of any language in the analysis of social interaction. As a step forward in the analysis of interrogative sentences in English and Spanish, this research presents relevant data which can be used in the teaching of English as a second foreign language in most schools in Cuba, as well as Spanish to foreign students.